LIFE HISTORY AND LARVAL PERFORMANCE OF THE COMMON TIGER BUTTERFLY, DANAUS GENUTIA CRAMER (LEPIDOPTERA; RHOPALOCERA; DANAIDAE) - J. B. ATLURI; M. BHUPATHI RAYALU; D. SANDHYA DEEPIKA (The Bioscan, 2010)
For the first time, the life history of the Common tiger butterfly, Danaus genutia and larval performance in terms of food consumption and utilization, and the length of life cycle was described its host plant Pergularia daemia. Our study was conducted during 2007 at Visakhapatnam (17º42’ N and 82º18’ E), South India. Danaus genutia completes its life cycle in 19.80 ± 1.10 days (eggs 3, larvae, 8 – 10, pupa 7 – 8 days). The values of nutritional indices across the instars were AD (Approximate Digestibility) 52.23 – 93.88%; ECD (Efficiency of Conversion of Digested food) 2.97 – 50.82, ECI (Efficiency of Conversion of Ingested food) 2.79 – 26.54, measured at the temperature of 28 ± 20 C and RH of 80 ± 10% in the laboratory. These relatively high values of ECD and ECI explain at least partially the ecological success of D. genutia in the present study environment.